Using more effective instructional verbs to elevate auditors' professional scepticism. Issue 2 (6th February 2022) - Stepankova, Sarka; Harding, Noel; Mayorga, Diane M.; Trotman, Ken T.
Abstract : We investigate whether using different instructional verbs to codify requirements in auditing standards, and to direct auditors in meeting those requirements, impacts the level of professional scepticism reflected in auditor judgments and the evidence auditors intend to collect. In an experiment, with practicing auditors serving as participants, we test whether directing auditors with higher order instructional verbs (e.g., consider and evaluate), rather than with lower order instructional verbs that are currently employed (e.g., review and identify), elevates auditors' professional scepticism. We investigate the level of professional scepticism reflected in two auditor judgments and the evidence that auditors intend to collect. Although we find that different instructional verbs did not have an effect on the level of scepticism reflected in auditor judgments, the use of higher order instructional verbs did elevate the level of scepticism reflected in the evidence auditors intend to collect. Our finding has important implications for the way in which auditing standards are drafted and the way in which auditors are guided by written instructions.